The Influence Of Service Quality, Facilities, And Trust On Patient Satisfaction At UPT Puskesmas Pal Three Pontianak - Nuraini Widya Sari; Haji Helman Fachri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of service quality, facilities, and trust on patient satisfaction at the Pal Tiga Community Health Center (Puskesmas) in Pontianak. The research is motivated by the essential role of primary healthcare services in ensuring public satisfaction with health services. A quantitative associative approach was used, with data collected through questionnaires distributed to 100 selected respondents. Data were analyzed using multiple linear regression with the assistance of SPSS version 22. The results indicate that service quality, facilities, and trust simultaneously have a significant effect on patient satisfaction. However, partially, only the trust variable has a significant influence on patient satisfaction, while service quality and facilities do not show significant individual effects. The coefficient of determination (R²) is 0.897, indicating that 89.7% of the variation in patient satisfaction can be explained by these three independent variables. These findings emphasize that building patient trust is key to enhancing healthcare service satisfaction.